Pengaruh Main Overhaul pada Boiler Terhadap Kinerja Menggunakan Metode Direct - Salsabila Gina Nursyfa; Ika Yuliyani; Ratu Fenny Muldiani (Fakultas Teknik UMRI, 2024)
Boiler performance is critical for optimal operation, so it requires continuous monitoring to prevent performance degradation. Decreased performance can be caused by drying, reduced fuel and feed water quality, and poor maintenance. One preventive measure is to carry out an overhaul. This research analyzes the effect of overhaul on boiler performance using data before and after overhaul, with a focus on the evaporation ratio and boiler efficiency. The research results show an increase in the evaporation ratio from 17.26 to 18.23 and efficiency from 77.12% to 79.56% after overhaul. This increase shows that the overhaul has succeeded in improving boiler performance. Increased boiler performance occurs as a result of overhaul activities, which include cleaning and replacing equipment. This maximizes heat transfer between the feed water and the gases resulting from fuel combustion.